Optimization and model-based control of sustainable ethyl-methyl carbonate and diethyl carbonate synthesis through reactive distillation. (10th October 2022) - Ge, Xiaolong; Han, Yicheng; Liu, Pengfei; Liu, Botan; Liu, Botong
Abstract: As excellent solvents of lithum-ion electrolyte, ethyl-methyl carbonate (EMC) and diethyl carbonate (DEC) are synthesized through transesterification of dimethly carbonate (DMC) and ethanol. Process intensification, optimization and the corresponding control scheme of the synthesized process are essential when sustainability is becoming a necessity. In the present work, the intensified flowsheet for EMC and DEC production process was firstly proposed and optimized with conventional reactive distillation (RD) and reactive dividing wall column (RDWC), respectively. Compared with RD process, RDWC could achieve 25.3% and 8.2% total annualized cost reduction for EMC and DEC production process, respectively. And carbon dioxide emission could be decreased by 29.4% and 11.7% by further integrating RD and separation column into RDWC arrangement for DEC and EMC production. Then multi-loop PI control schemes were developed as benchmark and linear model predictive controller was designed to handle the persistent feed disturbance. The superiorities of model-based controllers for the strongly interactive and coupled system are demonstrated by the dynamic response comparisons in terms of settling time, overshoot and integral of squared error (ISE), especially for the controlled variables with poor control performance under conventional multi-loop PI control structure. To summarize, the comprehensive control performance index-ISE with MPC is reduced by 55.9%–99.1%, as compared to those under PI control strategy. Highlights: Sustainable processes were realized by RD and RDWC for EMC and DEC production. Optimization was conducted for series sustainable processes with genetic algorithm. RDWC shows superiority in energy efficiency enhancement and CO2 emission reduction. Controllability investigation for sustainable processes with novel control strategy. Model predictive control shows to be effective for strongly coupled system.